Importance of Micromonospora spp. as Colonizers of Cellulose in Freshwater Lakes as Demonstrated by Quantitative Reverse Transcriptase PCR of 16S rRNA - de Menezes, Alexandre B. (American Society for Microbiology, 2012)
The relative abundance of micromonosporas in the bacterial communities inhabiting cellulose baits, water columns, and sediments of two freshwater lakes was determined by quantitative PCR (qPCR) of reverse-transcribed 16S rRNA. Micromonospora spp. were shown to be significant members of the active bacterial population colonizing cellulosic substrates in the lake sediment, and their increased prevalence with greater depth was confirmed by enumeration of CFU.